A brief review of the rapid transformation of driveline lubricants for hybrid electric and electric vehicles - Newcomb, Timothy (Frontiers in Mechanical Engineering, 2023)
Hybrid electric and electric vehicles have represented a small portion of the automotive market for many years and mainly use current lubricants, typically automatic transmission fluids (ATFs). However, regulatory compliance to limit greenhouse gases and increased consumer demand have resulted in a rapid global transition to electrified vehicles. This has prompted the need for new advances in vehicle technology to improve efficiency and thereby increase range. Enabling and optimizing such advances requires a new generation of driveline lubricants. Incorporating an electric motor in a transmission or axle, where the motor is exposed to the gear box lubricant, creates new challenges that focus attention on lubricant characteristics that were previously not differentiating features, for example, electrical and thermal properties. Additionally, lubricants must now also be compatible with the constituents used in electric motors which include new polymeric materials and, in some cases, exposed copper. Compatibility tests of these polymers vary within the industry and the risk of copper corrosion in these applications is not always properly assessed by current specification tests. In this paper we will begin with a brief history of electric vehicles, highlight how driveline lubricants, specifically ATFs, have evolved over the years to meet new hardware requirements and then describe the performance requirements expected of lubricants specifically designed for vehicles with electric drive units (EDUs). Our primary goal, however, is to summarize the recent literature that illustrates the changing importance of various lubricant performance properties, new proposed test methods and offer some insight into future e-lubricant evolution.